The Study of Symmetry Energy in Pasta of Neutron Star From Compressible Liquid Drop Model Approximation - Sulistyani, Eko Tri; Ananda, Rizky (Proceeding International Conference on Science and Engineering, 2019)
The properties of pasta which is located at the bottom of inner crust from neutron star has been studied by using compressibl e liquid drop model. Compressible liquid drop model is a modified liquid drop model as a density function. Liquid drop model based on assumption that the magnitude of nucleus bonding energy is contribution of surface, Coulomb, volume, symmetry, and proton -neutron pair effect. Pasta of neutron star behaves like liquid crystals (mesomhorpic phase). The top layer of pasta filled by free neutron gas, while in the lowest layer of the pasta is filled by proton-neutron gas. The properties of pasta are observed at temperatures close to zero Kelvin with the assumption that neutron star is on ground state and non accretion. The study of pasta emphasizes on symmetry energy’s influence. Symmetry energy reduces the magnitude of bonding energy of nucleon in the nucleus and it causes nucleon to be more easily released from nucleus. After that, symmetry energy influence the properties of pasta, such as the shape of nucleus that is non spherical (some like plates, rods, and bubbles), the fluctuative values of Wigner-Seitz cell, and uneven distribution of protons and neutrons in the pasta region of neutron star.